Implementasi Pemungutan Pajak Hotel dan Restoran Berbasis Sistem Online dalam Meningkatkan Kepatuhan Wajib Pajak Hotel Dan Restoran di Badan Pendapatan Daerah / Pasedahan Agung Kabupaten Badung - Dwi Naramaya, Ni Gusti Ayu Riris; Yasintha, Putu Nomy; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2018)
ABSTRACT This policy was implemented in 2013 by implementing an online system. This online system-based Hotel and Restaurant Tax Collection includes a reporting system (SPTPD), payment system, and online business transaction monitoring (supervision) system. With the existence of this policy, many conveniences were brought in. For taxpayers, they can carry out their obligations to report and pay taxes online. In this research, researchers used descriptive qualitative methods.To able to obtain data, researchers goes down to the field to observe and got a primary data and secondary data for documentation study. The implementation has been running quite well but, implementation it has not been able to improve the compliance of taxpayers. There are some difficulties in carrying out this policy, there are taxpayers who still use manual systems, taxpayers who are less cooperative in paying taxes, taxpayers do not make good use of the facilities provided, and less competent human resources. Keywords: Implementation, Public Policy, Tax, Online System